Psychological bias of employees and its impact on the high performance of human resources An analytical study of the opinions of a sample of employees in the Misan Governorate Health department - Mohammed Najm Abed Saleh / Dhurgham Hassan Abdily ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The purpose of the study is to explore the influence relationships between the psychological bias of employees through its sub-dimensions and the high performance of human resources at the level of a sample of employees in the Misan Governorate Health department, the questionnaire was adopted as a main tool in collecting data on the study sample, which numbered (130) individuals, represented by employees in the Misan Governorate Health department, many conclusions were reached through the study, the most important of which is the existence of a significant impact relationship of the psychological bias of employees on the high performance of human resources at the level of the study, the study also presented a number of recommendations, the most important of which is the need to pay attention to spreading awareness about the psychological bias of employees in the researched organization and all organizations.